Factors that influence teachers not to develop the strategies to improve the correct classroom management with an english language environment. - Espinoza Jaramillo, Sayuri Gemita (Machala : Universidad Técnica de Machala, 2015)
Los factores que afectan a la gestión bajo la lengua, en primer lugar es la aceptación de los maestros que de manera irresponsable aceptar el papel de la enseñanza del idioma Inglés, sin ningún conocimiento sobre el tema. Esto nos lleva a un estudiante no tiene ningún interés en el idioma Inglés, pero el maestro debe crear un entorno adecuado en el aula ya que esto es muy importante, el aula es la gestión de la supervisión y el control efectivo que el profesor pone a sus estudiantes con el fin de crear y mantener en sus clases y un medio ambiente saludable que favorezcan la atención y el trabajo mental intenso, contribuye al desarrollo de los estudiantes hábitos fundamentales de orden, la disciplina y el trabajo, y para inculcar un sentido de responsabilidad.
The factors that affect the low language management, in the first place is the acceptance of teachers who irresponsibly accept the role of teaching English language, without any knowledge on the subject. This leads us to a student does not have any interest on the English language, but the teacher must create an appropriate environment in the classroom already that this is very important, the classroom is the management of effective supervision and control that the teacher puts his students with the purpose to create and maintain in their classes and a healthy environment conducive to the attention and the mental work intense, helps develop students fundamental habits of order, discipline and work, and to inculcate a sense of responsibility.
Keywords: FACTOR; INFLUENCE; TEACHER; DEVELOP; STRATEGY